Risk of Stunting in Newborns - Ribkha Itha Idhayanti; Siti Musringah; Masini Masini (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2022)
The condition of the body being short and very short to exceed the deficit of -2 SD below the median length or height of the child is called Stunting. Stunting is also an impact caused by malnutrition from before pregnancy, during pregnancy or because there are comorbidities in pregnancy. Stunting can occur when a newborn is born. The length category of a newborn is based on the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2020 concerning Child Anthropometric Standards. Assessment of the nutritional status of children, the length of the baby boy is said to be short (stunting) if 46 cm and said to be tall if 53.7 cm. Meanwhile, the length of a baby girl is categorized as short (stunting) if it is 45.4 cm and is said to be tall if it is 52.9 cm. Many factors affect stunting at the time of newborns, namely teenage pregnancy, KEK pregnant women, pre-pregnancy BMI, chronic hypertension, and maternal height. This study was conducted to determine the relationship between risk factors in pregnant women and the incidence of stunting in newborns. This study aims to determine the general description of risk factors in pregnant women and the relationship between maternal risk factors in newborns. This type of research is quantitative research with a retrospective design. The tools and materials in this study used secondary data in the cohort and RM in the Banjarnegara 2 Health Center area, with a population of all mothers giving birth at the Banjarnegara 2 Health Center in 2019. The sample was taken from the population, the researchers used purposive sampling with a total sample of 300 respondents. with the Che square test. The results of this study showed that most respondents with non-adolescent pregnancies were 292 (97.3%), pregnant women did not have SEZ 277 (92.3%), ideal BMI 286 (95.3%), not chronic hypertension (96%), high maternal body weight 150, 280 (93.3%) and 283 (94.3%). There is a relationship between teenage pregnancy, CED in pregnant women, pre-pregnancy BMI, and maternal height with the incidence of stunting in newborns with a p value of 0.00 or p value 0.05, which means that there is a relationship between these variables and the incidence of stunting. in newborns.